DAMPAK KEBERADAAN INFRASTRUKTUR TERHADAP PENINGKATAN PRODUKSI DAN LUAS LAHAN SAWIT - Irawan, Andi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
The purpose of this research was analyzing the impact of the existence of infrastructures such as construction, electrical, highway (state, province and regency city road ), Transport and Telecommunication sectors on the production and areal expansion of oil palm plantations in both South Sumatera and Bengkulu. This research was expected to be useful as a scientific empirical guidance for policymakers in determining the infrastructure priority scale which is built based on their contribution to increasing oil palm production and its area. The research empirically identified how the impact of the existence of infrastructure (construction, electricity, highways (state, province, and city districts road), transport and telecommunication on the oil palm’s production and erea, in both its magnitude and sign. In the regression equation which used in this study, production and land area are positioned as dependent variable whereas development variables of construction, electricity, highway (state road, province and regency/city road), transport and telecommunications are positioned as the independent variable. This research used time-series data from BPS publications with quarterly periods from 1996 to 2012. Referring to the parameter of the elasticity value of infrastructure to oil palm production which showed greater than 1, then it can be concluded that the priority infrastructure which built in Bengkulu is the construction and for South Sumatra should be built electricity infrastructure to boost the oil palm production increasing. Meanwhile, electricity infrastructure that should be built for boosting the expansion of oil palm in Bengkulu is Electricity. There was relatively no priority infrastructure in terms of spurring the expansion of palm oil.